SOSYOLOJİ AÇISINDAN KAMU BÜROKRASİSİNDE MEMURLAR VE MEMURLUK BİLİNCİ (ELAZIĞ UYGULAMASI) - AYTAÇ, ÖMER (Fırat Üniveristesi, 1996)
This doctoral dissertation report is a product of the field research on the employees in public bureaucracy commissioned at the provincial government-building in Elazığ and officialdom consciousness of these civil servants attached to their profession by them front a sociological perspective. It mainly deals with their formal relationships at their workplace as well as their informal social relationships outside bureaucracy. The research report is formed of the two main sections. The first section consist of topics such as explanations of the key concepts including officialdom consciousness; delineation of the research problem; the aim of the research; delineation of the research problem; the methodology and research techniques and tools used in gathering, classifying and analyzing the data obtained. The methodological purpose of the research has been designated as exploratory. The second and more important section of this research report indicates analysis and explanations of the findings of the research including issues such as their personal and professional characteristics which effect their daily lives, occupational activities and achievements; in the formal and informal settings; the solutions to such problems expressed by them; their expectancies; their social relationships in bureaucracy; the prestige and meaning of their official career for them; and their personal opinions on the present issues of Turkey today.
Civil servants in public bureaucracy and their officialdom consciousness: A sociological perspective (Elazığ survey)
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Kamu Yönetimi; Public Administration; Sosyoloji; Sociology